العطاء الفکرى لحفیید رانجاناثان:البروفیسور شباهت حسین - د.رباح فوزى (المجلة الدولية لعلوم المكتبات والمعلومات)
This study deals with Library and Information Science in India, as anintroductory entry to the biographic, bibliographic and bibliometrics study of theintellectual productivity of Professor Shabahat Husain (1982-2017). The totalnumber of works reached 40 topics on periodicals, conference works, books. Thestudy used bibliometric methodology to analysis the productivity.